Who Moonlights and Why?: Evidence from the SIPP - Jean Kimmel; Karen Smith Conway (W.E. Upjohn Institute for Employment Research, 1995)
Multiple job-holding is a significant characteristic of the labor market, with approximately 6 percent of all employed males reporting a second job in 1993 (Mishel and Bernstein, 1995, p. 226). Moonlighting reflects growing financial stress arising from declining earnings, as well as an increased need for flexibility to combine work and family. Approximately 40 percent of moonlighters report taking the second job due to economic hardship. Additionally, moonlighting is a reflection of the worker's choice to pursue entrepreneurial activities while maintaining the financial stability offered by the primary job. To restate in economic terminology, moonlighting arises from at least two distinct reasons. First, many individuals hold multiple jobs due to some sort of constraint on the primary job that limits that job's earnings capacity. Second, moonlighting may arise because the labor supplied to the two jobs are not perfect substitutes. That is, the wage paid and utility lost from the forgone leisure may not completely reflect the benefits and costs to working. For example, working on the primary job may provide the worker with the credentials to acquire a higher paying second job, such as a university psychologist testifying in a jury trial. Or, working on the second job may provide some satisfaction not received in the same amount or manner from the primary job, such as a comedian who has a "regular" job by day and performs at night. In either example, the costs and benefits of both jobs are more complex than the monetary wages paid and the forgone value of leisure. When faced with such nonpecuniary benefits and costs, optimizing behavior may lead a worker to take two jobs. In contrast to workers who moonlight because they are constrained on their primary jobs (PJ), we expect these kinds of moonlighters to moonlight for longer periods of time because optimizing behavior leads them to supply labor to more than one job, even in the long run. We might also expect to see smaller wage differences between jobs for such workers and the second job (SJ) wage could even be higher than the primary job wage in some situations. Previous research on moonlighting, including Shishko and Rostker (1976), O'Connell (1979) and Krishnan (1990), acknowledges that multiple motives may exist but focuses only on the constraint motive. In related studies, Paxson and Sicherman (1994) explore moonlighting as an alternative avenue for adjusting short-run labor supply, and Abdukadir (1992) examines the possibility that moonlighting is caused by short-term liquidity constraints. Another possible motivation for moonlighting is that certain types of job situations present greater opportunities for tax evasion. Plewes and Stinson (1991) provide survey evidence from the 1989 Current Population Survey of the many distinct reasons for moonlighting reported by workers. The only research in the moonlighting literature that models the joint motives for moonlighting correctly while controlling for the endogeneity of primary job hours are Lilja (1991) and Conway and Kimmel (1994). The latter improves upon Lilja (1991) by specifying a more plausible utility maximizing model and developing a superior instrument for PJ hours. This research examines the characteristics of moonlighters and the length of their moonlighting episodes with the goal of understanding who moonlights and why. The data are for prime-aged men and are drawn from the 1984 Survey of Income and Program Participation (SIPP) panel. The primary advantages of the SIPP are the detailed information provided on up to two jobs (including job start and end dates) and the relatively short length of time (four months) covered by each interview of the survey. Both of these qualities make it possible to identify brief (as well as long) periods of moonlighting, movements into and out of jobs, and the characteristics associated with each job. Because moonlighting may be motivated by short-term financial needs, being able to observe short moonlighting durations is important. We begin by studying the personal and job-related characteristics of moonlighters and how the length of the moonlighting episode varies with these characteristics. We then estimate a duration model with unobserved heterogeneity to identify formally the determinants of moonlighting behavior when multiple motives may exist. Our expectation is that individuals who moonlight because they are constrained on their primary jobs might do so for shorter periods than those who are "job-packaging." Therefore, the hazard rate for workers who moonlight because of primary job constraints should be greater than for those with alternative motives, ceteris paribus. The mixed hazard function will vary as the composition of the sample changes with the duration of the moonlighting episode. By exploring the importance of heterogeneity and the direction of duration dependence of the mixed and structural hazard functions, we gain new insights into the determinants of moonlighting behavior. The descriptive analyses reveal that most moonlighters in our sample work full-time on their primary jobs and 15 to 20 hours a week on lower paying second jobs, and, in spite of those long hours, tend to be poorer than the average worker. Yet, a significant minority earns a higher wage on their second job. Our duration model results suggest that the structural hazard increases over time and there is significant unobserved heterogeneity. Taken together, these results are consistent with the presence of multiple motives for moonlighting, with the constraint motive being the most common.
Keywords: J0; J2; 330; moonlighting; jobs; Kimmel; Conway